Proses Adaptasi Komunikasi Lintas Budaya Antara Pegawai Hotel Masainn dan Tamu Internasional (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Bali, as an international tourism destination, serves as a space for cross-cultural interactions that require effective communication skills, particularly in the hospitality sector. Hotel Masa Inn serves predominantly international guests, requiring front office staff to adapt to cross-cultural communication. This study aims to analyze the process of cross-cultural communication adaptation between Hotel Masainn employees and international guests through the perspective of Willingness to Communicate (WTC). A descriptive qualitative approach was employed using observation, structured interviews, and document analysis. Informants were selected purposively from front office staff. The findings indicate that communication adaptation is carried out through basic English proficiency, the use of nonverbal communication, active interaction, and intrinsic motivation to improve language skills. However, this process also faces challenges in the form of communication anxiety and situational pressure, particularly when dealing with repeater guests. Within the WTC framework, employees’ willingness to communicate is influenced by self-confidence, motivation, anxiety, and interactional context, which collectively contribute to service quality and international guest satisfaction.